Concordance of B‐ and T‐cell responses to SARS‐CoV‐2 infection, irrespective of symptoms suggestive of COVID‐19. Issue 11 (30th July 2022) - Österdahl, Marc F.; Christakou, Eleni; Hart, Deborah; Harris, Ffion; Shahrabi, Yasaman; Pollock, Emily; Wadud, Muntaha; Spector, Tim D.; Brown, Matthew A.; Seow, Jeffrey; Malim, Michael H.; Steves, Claire J.; et al.
Abstract: This study assessed T‐cell responses in individuals with and without a positive antibody response to SARS‐CoV‐2, in symptomatic and asymptomatic individuals during the COVID‐19 pandemic. Participants were drawn from the TwinsUK cohort, grouped by (a) presence or absence of COVID‐associated symptoms (S+, S−), logged prospectively through the COVID Symptom Study app, and (b) anti‐IgG Spike and anti‐IgG Nucleocapsid antibodies measured by ELISA (Ab+, Ab−), during the first wave of the UK pandemic. T‐cell helper and regulatory responses after stimulation with SARS‐CoV‐2 peptides were assessed. Thirty‐two participants were included in the final analysis. Fourteen of 15 with IgG Spike antibodies had a T‐cell response to SARS‐CoV‐2‐specific peptides; none of 17 participants without IgG Spike antibodies had a T‐cell response ( χ 2 : 28.2, p  < 0.001). Quantitative T‐cell responses correlated strongly with fold‐change in IgG Spike antibody titer ( ρ  = 0.79, p  < 0.0001) but not to symptom score ( ρ  = 0.17, p  = 0.35). Humoral and cellular immune responses to SARS‐CoV‐2 are highly correlated. We found no evidence of cellular immunity suggestive of SARS‐CoV2 infection in individuals with a COVID‐19‐like illness but negative antibodies.